PRODUCTION OF EMBBRYONIC STEM CELLS FROM INNER CELL MASS OF BLASTOCYST ISOLATED BY ENZYMATIC AND IMMUNOSURGERY METHODS - Mata Hine, Thomas; Supriatna, Iman; Sajuthi, Dondin; Boediono, Arief (Jurnal Veteriner; Vol 9 No 1 (2008), 2008)
The objective of the research is determining the ICM isolation method to produce ESC. Blastocyst stage of DDy mice embryos were used in this study. Zona pellucida of blastocysts were removed by 0.25% pronase, the ICM isolation were done by enzimatic or immunosurgery method, and then they were cultured in DMEM-high glucose supplemented with mercaptoethanol, gentamycin, fetal bovine serum, and cumulus cells as feeder layer. The result of the research indicated that immunosurgery method yielding attachment rate and number ESC colony 93.85% and 43.08%, respectively, higher (P<0.05) than enzimatic method that weree 79.63% and 18.52%, respectively, but the viability of ICM cells were equal (P >0.05) that are 93.59% in enzymatic method and 98.56% in immunosurgery method. This research concluded that immunosurgery more effective method for isolation of ICM and ESC production than enzymatic method.
Keywords: embryonic stem cells, inner cell mass, enzimatic, immunosurgery